Bibliometric Analysis of Vaccine Trends and Novelty to Prevent Human Papillomavirus (HPV) Infection in Pregnant Women - Rahayu, Sri; Damayanti, Fitriani Nur; Defalia, Mas Ayu Thesi; Betri, Heni; Ambarwulan, Eradian (Jurnal Kebidanan, 2025)
Human papillomavirus (HPV) is the most common viral infection of the genital tract. Human papillomavirus (HPV) is associated with cervical, vulvar, and vaginal cancers in women, penile cancer in men, anal cancer, and oropharyngeal cancer in both. The biomolecular profile of Human Papillomavirus (HPV) has been widely studied in patients treated for HPV-related cervical lesions. Prophylactic vaccination against HPV is recommended as part of the vaccination schedule in many countries. This study aims to determine the trend in the number of publications, visualization of the relationship between the topic of vaccines to prevent human papillomavirus (HPV) infection in pregnant women through bibliometric analysis. The research method used a systematic review with stages following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) diagram. Data on scientific publications related to vaccines to prevent human papillomavirus (HPV) infection in pregnant women were taken through dimensions.ai from 2010 to 2023. The data were then analyzed using Vosviewer. This study produced the following findings. First, the number of publications and citations on the topic of vaccines to prevent human papillomavirus (HPV) infection in pregnant women has increased exponentially from year to year. Second, there are 135 items, 5 clusters, 5463 links, and 14809 link strengths on the topic of vaccines to prevent human papillomavirus (HPV) infection in pregnant women. Third, the suggested research topics related to vaccines to prevent human papillomavirus (HPV) infection in pregnant women are topics that have low density in the low category, namely high prevalence and vaccine hesitancy. The findings of this study can help relevant researchers to recognize trends and novelties in research on vaccines to prevent human papillomavirus (HPV) infection in pregnant women and recommend directions for future research.